Effectiveness of a respiratory rehabilitation program including an inspiration training device versus traditional respiratory rehabilitation: a randomized controlled trial - Sánchez-Milá,Zacarías; Abuín-Porras,Vanesa; Romero-Morales,Carlos; Almazán-Polo,Jaime; Velázquez Saornil,Jorge (PeerJ, 2023)
Background In the context of COVID-19, respiratory training is vital for the care and recuperation of individuals. Both exercise-based and instrumental respiratory training have been employed as interventions to enhance respiratory function, providing relief from symptoms in those impacted by the virus. The aim of this study was to evaluate the efficacy of two different respiratory rehabilitation programs. Methods A total of 200 participants affected with COVID-19 respiratory sequels were recruited, with a block randomization regarding sex to ensure equal and appropriate applicability of the results. An experimental controlled and randomized study was conducted, with participants engaging in a 31 days respiratory rehabilitation program, (a) experimental group, inspiratory training device combined with aerobic exercise and (b) traditional respiratory exercises combined with aerobic exercise. Results Both groups improved in cardiorespiratory parameters, with a decrease in systolic and diastolic pressure, dyspnea and lower limbs fatigue, and increased oxygen saturation, 6 min walking distance, diaphragmatic thickness, forced vital capacity, forced expiratory volume during the first second, peak expiratory flow rate, forced inspiratory vital capacity and maximal inspiratory pressure. Comparison between groups showed statistically significant differences in all variables except for oxygen saturation, 6 min walking distance and diaphragmatic thickness. The results of this study support the use of specific inspiration training devices for respiratory rehabilitation in COVID-19 sequels.
Keywords: Pulmonary rehabilitation; COVID-19; Ultrasound imaging; Sex-mediated differences